Typology of modifications to peer support work for adults with mental health problems: systematic review. (June 2020) - Charles, Ashleigh; Thompson, Dean; Nixdorf, Rebecca; Ryan, Grace; Shamba, Donat; Kalha, Jasmine; Moran, Galia; Hiltensperger, Ramona; Mahlke, Candelaria; Puschner, Bernd; Repper, Julie; Slade, Mike; et al.
Abstract : Background: Peer support work roles are being implemented internationally, and increasingly in lower-resource settings. However, there is no framework to inform what types of modifications are needed to address local contextual and cultural aspects. Aims: To conduct a systematic review identifying a typology of modifications to peer support work for adults with mental health problems. Method: We systematically reviewed the peer support literature following PRISMA guidelines for systematic reviews (registered on PROSPERO (International Prospective Register of Systematic Reviews) on 24 July 2018: CRD42018094832). All study designs were eligible and studies were selected according to the stated eligibility criteria and analysed with standardised critical appraisal tools. A narrative synthesis was conducted to identify types of, and rationales for modifications. Results: A total of 15 300 unique studies were identified, from which 39 studies were included with only one from a low-resource setting. Six types of modifications were identified: role expectations; initial training; type of contact; role extension; workplace support for peer support workers; and recruitment. Five rationales for modifications were identified: to provide best possible peer support; to best meet service user needs; to meet organisational needs, to maximise role clarity; and to address socioeconomic issues. Conclusions: Peer support work is modified in both pre-planned and unplanned ways when implemented. Considering each identified modification as a candidate change will lead to a more systematic consideration of whether and how to modify peer support in different settings. Future evaluative research of modifiable versus non-modifiable components of peer support work is needed to understand the modifications needed for implementation among different mental health systems and cultural settings.